2023
DOI: 10.1088/1748-605x/acd49c
|View full text |Cite
|
Sign up to set email alerts
|

A study on the antibacterial property and biocompatibility of ramie fiber

Abstract: Ramie fiber (RF) has excellent tensile strength and breathability, making it a promising material for biomedical applications. However, few studies on the antibacterial properties and biocompatibility of RF have been reported. This study aimed to investigate the antibacterial property and biocompatibility of RF with bacteria and fibroblasts. The results showed that the antibacterial activity of RF was better than that of natural cotton fiber (NCF) and close to that of medical cotton fiber (MCF) for both Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Ramie fibre (RF) is a traditional, widely used material in Asia, especially in China, which made it called as Chinese grass [1,2]. It is widely reported that RF has great antibacterial properties, so it has the potential for application in biomedical field [3,4]. In the study of Kandimalla R et al, it is reported that RF has perfect performance when it was used as a surgical suture [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ramie fibre (RF) is a traditional, widely used material in Asia, especially in China, which made it called as Chinese grass [1,2]. It is widely reported that RF has great antibacterial properties, so it has the potential for application in biomedical field [3,4]. In the study of Kandimalla R et al, it is reported that RF has perfect performance when it was used as a surgical suture [5].…”
Section: Introductionmentioning
confidence: 99%